Online Customer Reviews and Repurchase Intentions: Customer Satisfaction Mediation in Makassar Fast Food Consumers - Muhammad Ilham Wardhana Haeruddin; Isma Azis Riu; Muh Al Fatah Arief Putra; Nurul Rahmi Palangkey (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study examines the effect of Online Customer Reviews (OCRs) on repurchase intention and the mediating role of customer satisfaction among fast-food consumers in Makassar. Research Methodology: A quantitative, explanatory, and single cross-sectional survey was conducted involving 110 respondents selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. The analysis assessed the measurement model, structural model, direct effects, and the specific indirect effect. Results: OCRs had positive and significant effects on repurchase intention ((β=0.459\ p<0.001)) and customer satisfaction ((β=0.548\ p<0.001)). Customer satisfaction also positively influenced repurchase intention ((β=0.480\ p<0.001)). The indirect effect of OCRs on repurchase intention through customer satisfaction was significant ((β=0.263\ p<0.001)), indicating complementary partial mediation. Customer satisfaction accounted for 36.43% of the total effect, while OCRs and customer satisfaction jointly explained 68.2% of the variance in repurchase intention. Conclusions: Credible and relevant OCRs strengthen repurchase intention both directly and indirectly by shaping customer satisfaction. Repeat purchasing therefore depends on the consistency between expectations formed through digital reviews and the actual food and service experience. Limitations: The study was limited to fast-food consumers in Makassar and employed purposive sampling and a cross-sectional design, restricting broader generalization and causal inference. Contributions: The study integrates e-WOM theory, Expectancy-Disconfirmation Theory, and the Stimulus-Organism-Response model to explain how online reviews influence repurchase intention through customer satisfaction, while providing practical insights for review management and service improvement.